Efficiency and mechanisms of simultaneous removal of Microcystis aeruginosa and microcystins by electrochemical technology using activated carbon fiber/nickel foam as cathode material. (August 2020) - Lian, Huilan; Xiang, Ping; Xue, Yinghao; Jiang, Yuzhu; Li, Mengying; Mo, Jingyu
Abstract: The significant removal efficiency of microcystis aeruginosa was presented using Pt/Ti anode and activated carbon fiber/nickel foam (ACF/Ni) cathode by addition of Fe 2+ slightly in a wide range of initial pH (3–9). Results showed that about 93% of the Microcystis aeruginosa cells were removed within 15 min for Pt/Ti-ACF/Ni–Fe 2+ system. Dosage of Fe 2+, current density, and initial pH had remarkable effects on the removal efficiency of microcystis aeruginosa. The mechanism of algae removal in the Pt/Ti-ACF/Ni–Fe 2+ electrochemical system was revealed by the comparison between Pt/Ti-ACF/Ni–Fe 2+ process and classical Fenton process, the analysis on Microcystis aeruginosa and ACF/Ni by SEM, the specific surface area and pore size analysis of ACF, and the determination of UV254, OD620 and microcystin-LR (MC-LR). Results showed that the main mechanism of this system was the electro-Fenton process, which was accompanied by electro-adsorption, electro-floatation, and electro-coagulation process. And the cooperation mechanism on the electrochemical removal system was further speculated. With the breakdown of algal cells during the electrolysis, the MC-LR and other substances released from the cells were effectively degraded. Besides, the new cathode exhibited favorable and stable reusability. This study built up a high-efficiency algae removal system, which broke through the limits of narrow working pH range and large consumption of exogenous chemicals in electro-Fenton process. Highlights: A stable ACF/Ni cathode with good algal removal performance was constructed. The mechanism and cooperation mechanism were explored in the system. The reason of broadening the pH range was analyzed.